Glutamate regulation of Voltage-Gated Sodium Channels (VGSCS) in breast cancer cell lines of different metastatic potential - Azahar, Irfan Irsyad (2022)
The upregulation of voltage-gated sodium channels (VGSC) expression and activity, specifically its neonatal splice variant, nNav1.5, in human breast cancer is commonly related to metastatic potential. Concentration of a common neurotransmitter, glutamate is also found to be high in multiple types of human cancers, including breast cancer. This raises the potential of regulatory control by nNav1.5 on glutamate in breast cancer cells as in normal neuronal physiology (VGSC-glutamate). Thus, the overall aim of the study is to investigate the regulatory control of nNav1.5 on the glutamate concentration in breast cancer cells and its metastatic potential. Glutamate assay was conducted to compare basal concentration of endogenous and exogenous glutamate, glutamate staining for microscopy imaging of cellular glutamate and real-time PCR was conducted to compare the mRNA of nNav1.5 between the non-cancerous breast epithelial cell line (MCF-10A), the less aggressive human breast cancer cell line (MCF-7) and the highly aggressive human breast cancer cell line (MDA-MB-231). Since MDA-MB-231 was found to have significantly highest glutamate concentration along with upregulation of nNav1.5 mRNA expression, the cells were subjected for nNav1.5 inhibition using agents; siRNA, VGSCs specific blocker, tetrodotoxin (TTX) and glutamate released inhibitor, riluzole (at IC50 concentration produced from MTT assay). Cell growth and metastatic potential of the cells were also assessed by MTT and invasion assay, respectively. Glutamate concentration was detected in all the three cell lines, where the highest concentration detected in MDA-MB-231 cells (p<0.05). This was confirmed with fluorescence microscopy images showing prominent red staining in MDA-MB-231. nNav1.5 mRNA expression was also detected in all the three cell lines, again, with the highest expression in MDA-MB231 cells (p<0.01). The nNav1.5 mRNA expression was successfully knocked down using siRNA (p<0.01) in MDA-MB-231 cells, similarly, for MDA-MB-231 cells treated with TTX (p<0.01) and riluzole (p<0.05). Followed by significant reduction of endogenous and exogenous glutamate by TTX (p<0.05), siRNA (p<0.05) and riluzole (p<0.05) as confirmed by reduction of the red staining of glutamate by all the three treatments (p<0.05) through fluorescence microscopic imaging. Inhibition of glutamate by riluzole led to significant downregulation of mRNA expression of the metastatic biomarkers of the matrix metalloproteinase family, MMP1 (p < 0.01), MMP8 (p < 0.01), and MMP11 (p < 0.01) respectively, followed by suppression of 3D spheroid invasion by these agents. Accordingly, the untreated MDA-MB-231 3D spheroid invasion rate increased until day 3 and started to plateau. However, for the treated MDA-MB-231 3D spheroids, the perimeter diameter of the 3D spheroid plateaued throughout the 7 days experiments, indicating no observable invasion. In conclusion, nNav1.5 expression correlate with glutamate concentration and metastatic potential of breast cancer cells. Importantly here, this study showed for the first time a possible regulatory control of nNav1.5 on glutamate concentration and so does the metastatic potential of the cancer cell.